Acute kidney injury outcomes at 90 days at a South African academic hospital - Chothia, Mogamat-Yazied; Moosa, Mohammed Rafique (African Journal of Nephrology, 2022)
Background: Acute kidney injury (AKI) remains a serious problem in Africa. Most studies from sub-Saharan Africa are retrospective in design and report on only short-term, in-hospital outcomes. There remains a paucity of prospective data on the long-term outcomes of AKI in sub-Saharan Africa. Methods: We performed a prospective cohort study from 1 January to 30 June 2016. AKI was diagnosed and staged according to KDIGO AKI 2012 criteria. Patients attending an academic hospital in Cape Town, South Africa were followed up for 90 days or more. Outcome was a composite of either chronic kidney disease (CKD) (eGFR <60 mL/min/1.73 m2), end-stage kidney disease (ESKD) (eGFR <15 mL/min/1.73 m2) or death. Results: A total of 113 patients were included of whom 64 (57%) reached the composite outcome. Those reaching this outcome were older (47.5 years vs. 35 years, P = 0.02) and were more likely to have had a history of hypertension (35.9% vs. 16.3%, P = 0.02). The most common causes of AKI were sepsis (33%), drugs and toxins (16%) and glomerular disease (12%). Older age (OR 2.3, 95% CI 1.03–5.12, P = 0.04) and a history of hypertension (OR 2.9, 95% CI 1.15–7.17, P = 0.02) predicted the composite outcome on univariable logistic regression; however, only a history of hypertension was associated on the multivariable model (adjusted OR 1.27, 95% CI 1.04–1.56, P = 0.02). Conclusions: In African patients with AKI, the composite outcome of CKD, ESKD and death at 90 days or more was high. Interventions to prevent the progression of patients with CKD are needed because access to chronic renal replacement therapy in the public sector of South Africa is limited.